Vibration Suppression Through Variable Stiffness and Damping Structural Joints - Wang, Qinyu; Senatore, Gennaro; Jansen, Kaspar; Habraken, Arjan; Teuffel, Patrick (Frontiers in Built Environment, 2020)
This paper introduces a new semi-active strategy for vibration control of reticular structures (i.e. trusses and frames) equipped with variable stiffness and damping joints which consist of a shape memory polymer (SMP) core reinforced by an SMP-aramid composite skin. When the joints are actuated to the transition temperature through thermal actuation, the SMP core transitions from a glassy to a rubbery state through a viscoelastic region, which causes a stiffness reduction and an increase of damping. The mechanic behavior of the joint can be thought of as transitioning from a moment to a pin connection. This way, it is possible to cause a shift of the structure natural frequencies and to increase damping, which is employed to obtain a significant reduction of the dynamic response. This paper comprises two parts: 1) characterization of a variable stiffness and damping material model through experimental testing; 2) numerical simulations of a truss bridge and a four-story frame, which are equipped with variable stiffness and damping joints. The truss bridge (case A) is subjected to a resonance and a moving load while the four-story frame (case B) is subjected to El Centro earthquake loading. For case A under resonance loading, the dynamic response can be reduced exclusively through a frequency shift and ignoring viscoelastic effects. For case A under moving load and case B under earthquake loading, vibration suppression is mostly caused by the increase of damping due to viscoelastic effects. Control time delays due to joint heating have been included in the analysis. When the joints are actuated to the transition range 55-65°C, which is specific to the SMP adopted in this study, the acceleration peak amplitude reduces by up to 95% and 47%, for case A and case B, respectively. For both cases, damping increases by up to 2.2% from undamped conditions (25ºC). This work has shown that the adoption of variable stiffness and damping structural joints has great potential to enable a new and effective semi-active control strategy to significantly reduce the structure response under a wide range of dynamic loading conditions.